2017
DOI: 10.1063/1.4999763
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of the dielectric tensor of monoclinic Ga2O3 single crystals in the spectral range 1.0–8.5 eV

Abstract: The full dielectric tensor of monoclinic Ga2O3 (β-phase) was determined by generalized spectroscopic ellipsometry in the spectral range from 1.0 eV up to 8.5 eV and temperatures in the range from 10 K up to 300 K. By using the oriented dipole approach, the energies and broadenings of the excitonic transitions are determined as a function of the temperature, and the exciton-phonon coupling properties are deduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…Specifically, the optical properties of monoclinic β-Ga 2 O 3 were investigated in detail. Because of low crystal symmetry, phonon contributions [10,11] and interband transitions [11][12][13] are described by dielectric tensors containing four different nonzero tensor components. The Raman selection rules and tensor components are strongly influenced by the anisotropic properties of the material [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the optical properties of monoclinic β-Ga 2 O 3 were investigated in detail. Because of low crystal symmetry, phonon contributions [10,11] and interband transitions [11][12][13] are described by dielectric tensors containing four different nonzero tensor components. The Raman selection rules and tensor components are strongly influenced by the anisotropic properties of the material [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Generalized spectroscopic ellipsometry permits measurements of the optical properties of arbitrarily anisotropic materials, 36,72,73 including crystalline materials with monoclinic 37,[41][42][43][44]47,60,61,74 and triclinic symmetry. 75 The Mueller matrix is measured, and then compared with model calculations.…”
Section: Generalized Ellipsometrymentioning
confidence: 99%
“…36 For example, monoclinic β-Ga 2 O 3 , which has gained attention for high power solid state transistor and switch applications, has been analyzed from the terahertz to the vacuum ultra violet spectral regions for its complete phonon mode and free charge carrier properties, [37][38][39][40] and electronic band-to-band transitions as well as its static and highfrequency dielectric constants, indices of refraction, and extinction coefficients. [41][42][43][44][45] A similar analysis procedure resulted in complete sets of phonon modes for monoclinic scintillator material cadmium tungstate (CdWO 4 ) 46 and YSO. 47 To date, the only generalized spectroscopic ellipsometry investigation of LSO was reported by Jellison et al, and the four real-valued dielectric function tensor spectra were obtained in the spectral range from 200 nm to 850 nm.…”
Section: Introductionmentioning
confidence: 99%
“…A full study of n (λ, T ) in this oxide still needs to be further discussed. Indeed, even though it is of great importance for the application of this very relevant material in photonics, just a few studies have been reported [ 9 , 10 , 11 , 12 ]. The work by Bhaumik et al [ 10 ] used the prism method to obtain the refractive index at temperatures between room temperature (RT, 25 °C, i.e., 298 K) and 200 °C (473 K).…”
Section: Introductionmentioning
confidence: 99%